From culture to code: Integrating ethnomathematics into Scratch-based games to enhance students’ mathematical problem-solving - Astari Astari; Rahmat Nurcahyo; Muhadi Hariyanto; Dwi Yulianto (AXIOM : Jurnal Pendidikan dan Matematika, 2026)
The COVID-19 pandemic has widened gaps in mathematics achievement, underscoring the need for adaptive digital learning strategies. A preliminary diagnostic assessment conducted at SMPN 1 Leuwidamar, Banten, revealed significant weaknesses in students’ problem-solving skills, particularly in the looking-back stage of Pólya’s model. This study aimed to develop and evaluate a Scratch-based learning medium integrated with Baduy ethnomathematics to enhance students’ mathematical problem-solving abilities. Employing a Research and Development (R&D) approach based on the ADDIE model, the study involved 31 seventh-grade students. Data were collected through problem-solving tests, student and teacher questionnaires, and expert validation forms. The validation results indicated that the learning medium was highly feasible (mean = 0.93). Effectiveness testing revealed a significant improvement in problem-solving scores, increasing from an average of 62.40 to 81.20 (p < 0.001), with 84% of students meeting the mastery criterion and 32% achieving perfect scores. The greatest improvement was observed in strategy implementation (moderate-to-high category), whereas improvement in the initial understanding stage was relatively modest. Student responses were highly positive (mean = 93.92%), particularly regarding cultural relevance and learning motivation. These findings confirm that integrating Baduy ethnomathematics into Scratch-based learning media effectively enhances mathematical problem-solving skills while reinforcing cultural relevance in the learning process.